A Comprehensive Review of Bioinformatics Tools and Applications Revolutionising Aquatic Animal Health Management (Journal of Fish Health, 2025)
Aquatic animal health management is a critical aspect of maintaining the sustainability and productivity of aquaculture systems. The increasing complexity of aquatic ecosystems and the challenges posed by the emerging diseases necessitate innovative approaches for effective health management. Molecular medicine necessitates the integration and analysis of genetic, molecular, cellular, and clinical data, posing a unique set of problems to bioinformatics. Omics technologies give researchers the tools they help to examine differences in DNA, RNA, proteins, and other biological components within and between different species. Bioinformatics is indispensable in the field of fish health as it enables a deeper understanding of the genetic, molecular, and environmental factors that affect fish well-being. This review explores the application of bioinformatics in understanding, monitoring, and managing the health of aquatic organisms.